COVID-19: Work from home challenges faced and tackled by the employees during pandemic - Prof. Rajashree Bhise, Ms. Mili Haldar, Prof. Choden Goperma, Prof. Bhooshan Agalgatti Prof. Pandu Gowdara (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The Pandemic started from a city of China named Wuhan. The COVID-19 erupt was first observed on 17th November 2019. The person who got infected with Coronavirus first time and transformed into the source of this communicable infection was a fifty-five years old individual who is a resident in the Hubei locale. This started to spread when the individual communicated with a couple of individuals at a fish market. By and by the entire globe is experiencing pulverization and encountering prosperity and monetary crises